2012
DOI: 10.4103/0019-5049.96306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different formulations of local anaesthetics for cervical epidural anaesthesia during thyroid surgery

Abstract: Background:To compare the efficacy and safety of local anaesthetics under cervical epidural anaesthesia (CEA) using lignocaine (1%), bupivacaine (0.25%) and ropivacaine (0.5%) for thyroid surgery.Methods:In a prospective, randomized fashion, 81 patients were selected for thyroid surgery under CEA. They were assigned to one of three groups: Group L, B and R to receive 10 mL of 1% lignocaine, 0.25% bupivacaine and 0.5% ropivacaine, respectively. We compared their efficacy in terms of pulmonary and haemodynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A majority-72% (51/73), were either single case reports or case series. Among the comparative studies, five were RCTs, [55][56][57][58][59] with the rest (n=17) being either prospective or retrospective OCTs. 3 60-75 The outcome details and study characteristics for all the RCTs are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority-72% (51/73), were either single case reports or case series. Among the comparative studies, five were RCTs, [55][56][57][58][59] with the rest (n=17) being either prospective or retrospective OCTs. 3 60-75 The outcome details and study characteristics for all the RCTs are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…55 66 68 Among CRs, CEA was attempted as the sole anaesthetic in 36 /51 reports. However, the following four studies reported conversion to GA for various reasons: a tired patient was induced GA after two h; 8 two out of three cases required nitrous oxide (N 2 O) support, out of which one was cancelled because of decreasing consciousness; 26 one patient was intubated because of respiratory difficulty; 28 three patchy epidurals were converted to GA. 57…”
Section: Methods Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…Having used cervical epidural commonly for pain management, we choose to use CEA because of our familiarity with the technique. Cervical epidural anesthesia has been used for thyroidectomy, carotid artery surgery, and other neck surgeries [10,20,21,22]. Some of the advantages of CEA over the other forms of regional anesthesia include the ability to prolong anesthesia and provide excellent post-operative analgesia because of the placement of a catheter, and the sympathetic blockade produced reduces blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have observed the adverse events such as bradycardia, hypotension, and acute ventilatory failure due to the administration of high concentration local anesthetics. [ 20 21 ]…”
Section: Discussionmentioning
confidence: 99%